Newspaper ‘Gazavat’ and Issue of North Caucasus in Nazi Germany’s Propaganda in 1943-1944 - A. A. Tatarov (Научный диалог)
The newspaper ‘Gazavat’ is considered in the article as a source of printed propaganda by Nazi Germany among the mountain peoples of the North Caucasus in the national formations of the Wehrmacht. In Russian and foreign historiography, the materials of ‘Gazavat’ have been poorly studied and insufficiently introduced into scientific circulation. The aim of the article is to analyze the articles of ‘Gazavat’ for 1943–1944 in order to identify the content of Germany’s specialized propaganda aimed at the peoples of the North Caucasus. Based on content analysis and thematic analysis methods, the author identifies four thematic blocks: national history, political future, fighting spirit, and religion. The conducted research showed that Germany used well-thought-out political technologies to manipulate the real costs of integrating the North Caucasus into the Russian Empire and the USSR. The release of the newspaper ‘Gazavat’ for North Caucasus units of the Wehrmacht was significantly delayed. The specialized propaganda was aimed at converting traditional institutions, national hopes, and historical traumas of the mountain peoples into a call for retribution against the Soviet regime. At the same time, a combination of the potential and expert knowledge of mountain emigrants, German political and military actors was implemented.